Pengembangan E- Inventory Peralatan dan Perlengkapan Sekolah Pada SMK Satmanggi Siompu - Nawawi, Muhamad; Aswardi, Iko (ProTekInfo(Pengembangan Riset dan Observasi Teknik Informatika), 2024)
SMK Satmanggi Siompu is a private vocational high school located on Jalan Poros Siompu, Biwinapada Village, Siompu District, South Buton Regency, Southeast Sulawesi Province. The aim of this research is to understand the current inventory system, design a new system, conduct testing, and implement the system. It is hoped that the inventory information system for equipment and supplies at SMK Satmanggi Siompu can address issues related to inventory data collection and processing. The goal is to enhance performance in inventory data collection and processing. The information system encompasses hardware, software, database, and the user interface of the resulting system. The final stage of the research involves testing the software using the Black Box Testing method. The research method used is Research and Development (R&D), which aims to produce a specific product and test its effectiveness. Data collection methods are descriptive and involve using both primary and secondary data sources. The system-oriented approach uses object-oriented tools called Unified Modeling Language (UML). Analytical tools include use case diagrams, activity diagrams, sequence diagrams, collaboration diagrams, class diagrams, object diagrams, and component diagrams. The system development method uses the prototype method. The system is built using the Bootstrap framework, PHP programming language, and MySQL database